PEMANFAATAN PATI PISANG KEPOK (Musa balbisiana L.) TERPRAGELATINASI POSPAT SEBAGAI SUSPENDING AGENT SUSPENSI KLORAMFENIKOL - Deni Anggraini; Anita Lukman; Delvi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Kepok banana (Musa balbisiana L.) natural starch easily undergoes syneresis due to starch retrogradation which can reduce the stability and viscosity of a suspension preparation, so it is necessary to modify starch to overcome this problem. One of the starch modification technologies is chemical modification with crosslinks. Utilization of kepok banana phosphate pregelatinated starch (Musa balbisiana L.) as a suspending agent in chloramphenicol palmitate suspension has been carried out and evaluated for its physicochemical properties and stability during storage. The method of making the suspension is the dispersion method. F1 used 5% kepok banana phosphate pregelatinated starch, F2 (7.5%) and F3 (10%). The results showed that the best formula was F3 with observations of organoleptic, viscosity and flow properties, degree of sedimentation, redispersibility, density, and pH which met the requirements during 4 weeks of storage.